The effect of pubertal development on the sleep-wake cycle - Borrani Valdés, Jorge Benjamín; Valdez Ramírez, Pablo; Guerra, Gonzalo; Ramírez, Candelaria; García, Aída (2020)
To analyze if the delay of the sleep-wake cycle is the effect of pubertal development, independently of age or school grade. Methods: Girls and boys between 4th and 6th grade were divided into a low pubertal stage and a high pubertal stage group. Age and school grade were controlled to isolate the effect of puberty by pairing the groups on these variables. The regular bedtime, waking time, sleep duration and daytime sleepiness were obtained through questionnaires. A Pubertal Developmental Scale with questions about bodily changes was used to determine pubertal stage.